New Education Policy for Higher Education : Key features, merits and Challenges : A study - Dr. Anju Sharma; Dr. Seema Phogat (Innovative Research Thoughts, 2023)
This article argues that "system-wide excellence in student learning at a fair cost" may be achieved via education policies that diverge from the typical market-oriented reform methods used by many other nations. In this regard, Finland is a model knowledge economy, having transformed itself from a rural agricultural and industrial backwater in the 1950s by placing a premium on education as the means to economic and social progress. This article uses data from international student evaluations and past policy studies to demonstrate how Finland's equitable, flexible, innovative, professional, and trusting educational policies have led to sustained gains in student achievement. Finland has not implemented any policies to introduce externally decided learning standards or high-stakes testing into its education system. Sustainable leadership principles form the basis of Finland's educational policies, which put a premium on classroom instruction, encourage schools to foster conducive learning environments and apply curricula proven to help students succeed in the long run.